(3JCUjd GdHfG aj JYdjd GdHfGs - (3CHhYHO Gddg HOQGdOjf eMeO Hf YHO Gddg Hf HgGOQ GdRQcTj GdTGaYjs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3bGd(B: (3GHf eGdc aj NdGUJg(B: (3hGdGSe efg oeYQH heHfi dTHg ef GdMQha eOfi s
(3BNQgG (B:s
(3hGdPj jSJhLHg VQHGJ VQH jONdg GdJfhjf cLhGQ aj GdMGdJjf hVQH dG jONdg hdjcf gPG BNQ cdGefG Ydi gPG GdaUd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3fSNI KGfjI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3fSNI KGfjI ajgG VHW hHgG fXGe GdJYbjHIs
(3hYdi GdgGeT aj BNQgG YHGQI (B"(3HjGV aj CUd eDdag fMh SHYI CSWQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs